Homeless Outreach and Law Enforcement : A Community Based Partnership and Autoethnography - Fay, Martha J.; Schultz, Nicole J.; Brault, Erin (My University, 2018)
The aim of this project was to create an opportunity to meet community partner needs. The student researcher’s primary role was to collaborate with a local not-for-profit organization during the 2017-2018 academic year to develop plans for a pilot program for a homeless outreach team that would improve connections and services between mental health providers and local law enforcement. The primary goal of the homeless outreach team is to bridge the gap between local social service agencies and law enforcement often working with similar members of the homeless population in the area but not directly in support of one another. Through the use of observations, interviews, and interactions with members of each population, the research team developed an implementation plan and reinforced contact between members of law enforcement, staff at the local not-for-profit, and members of the homeless population. All of this was done with the intention of implementing this plan in the near future to create a sustainable, long-term, and positive partnership between these parties.
Color poster with text and images.
Keywords: Posters; Homeless; Social work; Law enforcement--Eau Claire; Mental health